Prevalence and Gender Distribution of Lower Arch Crowding - A Retrospective study - KAMDAR, RUSHABH; B, NIVETHIGAA; M, ARUN (The journal of contemporary issues in business and government, 2021)
Malocclusion is an irregularity or malalignment of teeth. Malocclusion can be either skeletal or dental. Several reasons exist that can result in the malocclusion, of which the most common is the tooth size arch length discrepancy. When the arch development is within the expected size or the size of the tooth is abnormally large, it can result in the crowding. Several other reasons have also been attributed with lower arch crowding. This study was done to assess the prevalence and gender distribution in patients with lower arch crowding. This study was carried out in an institutional setting. Data were collected regarding the lower arch crowding in the population and tabulated in the excel and transferred to statistical software SPSS. Descriptive statistics and chi square tests were done. Out of the total population (41545) , 5602 of them had lower arch crowding either alone or in combination with other malocclusion. Among those with lower arch crowding, 3067 of the males had only crowding and 293 had crowding in association with other malocclusion, whereas 1951 of the females had only lower arch crowding and 291 of them had crowding in association with other malocclusions. From the present study, we can conclude that the prevalence of crowding is relatively high(13.48%) compared to any other malocclusion. Higher male predilection in the study sample and more number of cases with crowding as the only malocclusion was also noted. Gender and age association showed a significant association with more numbers of males especially in the age group of 19-35 years in the study population had crowding.